Longitudinal associations between parental mental health and the duration of visual attention and facial expressions during at-home parent–infant interactions: a UK birth cohort study - Costantini, Ilaria; Kounali, Daphne; Culpin, Iryna; Bornstein, Marc H.; Pearson, Rebecca M. (Frontiers in Child and Adolescent Psychiatry, 2025)
BackgroundParental mental health difficulties have been associated with variation in parent–infant interactions, including facial expressions and visual attention. Most prior research has relied on clinical samples and structured observational settings, limiting ecological validity and generalisability to population-level variation.AimsThis study aimed to (i) characterise the duration of facial expressions and visual attention behaviours in parents and infants during naturalistic interactions at home, and (ii) explore associations between parental depressive symptoms and personality difficulties—measured prenatally or preconception—and these observed behaviours.MethodsInteractions were recorded at home using synchronised head-mounted cameras worn by parents and infants. Facial expressions and gaze behaviours were micro-coded for each dyad member using a validated behavioural coding system. Parental depressive symptoms and personality difficulties were assessed using the Edinburgh Postnatal Depression Scale (EPDS) and the Standardised Assessment of Personality—Abbreviated Scale (SAPAS). Associations were estimated using bivariate two-level models, adjusting for relevant covariates and clustering at the dyad level.FindingsA total of 142 video observations were obtained from 97 families participating in the Avon Longitudinal Study of Parents and Children (ALSPAC), including 102 unique parent–infant dyads. Of the 142 observations, 74% involved mothers as the primary caregiver. Infants were on average 7 months old, and 66% were first-born. We found suggestive evidence that higher parental depressive symptoms and personality difficulties were associated with shorter durations of expressions such as “mock surprise” and “woe face”, and with longer durations of negative affect. Infants of parents with higher depressive symptoms showed longer smiling and increased visual attention to others in the room, potentially reflecting social referencing.ConclusionsWearable cameras offer a feasible and ecologically valid method for observing parent–infant interactions in home settings. Findings suggest that variation in parental mental health is associated with differences in both parental and infant emotional and attentional behaviours. These preliminary results underscore the potential of wearable technology for advancing research on early relational processes.